2009
DOI: 10.4103/0019-5154.48976
|View full text |Cite
|
Sign up to set email alerts
|

Erythroderma : Review of a potentially life -threatening dermatosis

Abstract: Erythroderma, or generalized exfoliative dermatitis, is a disease characterized by erythema and scaling of greater than 90% of the body's surface. The resultant dysmetabolism is potentially life threatening. A detailed history is to identify and treat the underlying cause of this dermatitis. We present two cases of erythroderma in African patients and review this important disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 48 publications
3
46
0
10
Order By: Relevance
“…Currently, it is believed that the condition is secondary to an intricate interaction of cytokines and cellular adhesion molecules, including interleukins 1, 2 and 8, intercellular adhesion molecule 1 and tumor necrosis factor. 4,5 It is one of the most severe patterns of cutaneous drug reaction. It is a non-specifi c disease pattern induced by different diseases or medications.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is believed that the condition is secondary to an intricate interaction of cytokines and cellular adhesion molecules, including interleukins 1, 2 and 8, intercellular adhesion molecule 1 and tumor necrosis factor. 4,5 It is one of the most severe patterns of cutaneous drug reaction. It is a non-specifi c disease pattern induced by different diseases or medications.…”
Section: Discussionmentioning
confidence: 99%
“…There is also increased susceptibility to colonization of bacteria in erythroderma due to inflammation and fissuring of skin. This may lead to development of sepsis in susceptible individuals [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of cellular adhesion molecules ( Intercellular adhesion molecules, vascular cellular adhesion molecules, E selectins) are found in different types of erythroderma. There is a complex interaction between these adhesion molecules and cytokines which leads to increased mitotic and epidermal turnover rate which is clinically seen as scaling [1,8].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Freedberg and Baden, exfolia on more than 17 g/m 2 /day can lead to a nega ve nitrogen balance. 3 Later, Kanthraj et al observed that exfolia ve derma s may increase the daily protein loss by approximately 25-30% in psoriasis and by 10-15% in exfolia ve derma s due to other causes. Based on this observa on, they recommend early supplementa on of protein, in addi on to the normal balanced diet, for minimizing the nega ve nitrogen balance.…”
Section: Introductionmentioning
confidence: 99%
“…Even with an es mated annual incidence of 35 cases per 1,00,000 dermatology outpa ent visits represen ng 1-1.5% of total skin clinic admissions [1][2][3][4] , the exact e ology and overall ma nagement of exfolia ve derma s o en stands challenging. There exists a number of gaps in the understanding of the metabolic eff ects of exfolia ve derma s and its correc on.…”
Section: Introductionmentioning
confidence: 99%